2019
DOI: 10.1161/cir.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

2019 American Heart Association Focused Update on Advanced Cardiovascular Life Support: Use of Advanced Airways, Vasopressors, and Extracorporeal Cardiopulmonary Resuscitation During Cardiac Arrest: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care

Abstract: The fundamentals of cardiac resuscitation include the immediate provision of high-quality cardiopulmonary resuscitation combined with rapid defibrillation (as appropriate). These mainstays of therapy set the groundwork for other possible interventions such as medications, advanced airways, extracorporeal cardiopulmonary resuscitation, and post–cardiac arrest care, including targeted temperature management, cardiorespiratory support, and percutaneous coronary intervention. Since 2015, an increased number of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
419
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(502 citation statements)
references
References 69 publications
1
419
0
6
Order By: Relevance
“…From the 2019 ACLS guideline update, there were no survival benefits of high-dose E compared to standard-dose E [2]. Although few studies with large sample sizes have directly reported the toxicity of catecholamines, a number of case reports have documented the link between E overdose with a series of arrhythmia changes including sinus tachycardia, and idioventricular rhythm with multifocal premature ventricular complex [27] or ST elevation due to myocardial injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…From the 2019 ACLS guideline update, there were no survival benefits of high-dose E compared to standard-dose E [2]. Although few studies with large sample sizes have directly reported the toxicity of catecholamines, a number of case reports have documented the link between E overdose with a series of arrhythmia changes including sinus tachycardia, and idioventricular rhythm with multifocal premature ventricular complex [27] or ST elevation due to myocardial injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Only when conventional CPR efforts failed, and skilled physicians could quickly establish ECMO, ECMO might be considered as a rescue treatment. 23,24 Our found that MAP was associated with NSE and S100B protein (NSE and S100B were often used to evaluate the degree of brain injury). 27 Ameloot et al study included 112 out-of-hospital cardiac arrest patients, found that higher than reduces brain ischemia, and improves outcome.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ELSO registry, the incidence of ECPR use increased more than 10-fold between 2003 and 2014, from 35 to over 400 per year ( Figure 2) [6,7], and the overall survival to hospital discharge was 29% in adults [8]. The Advanced Cardiac Life Support (ACLS) Guidelines state that ECPR may be considered for selected patients as rescue therapy when CCPR efforts are failing in settings in which it can be expeditiously implemented and supported by skilled providers (class 2b; level of evidence, C-LD) [9,10]. However, there is insufficient evidence to recommend its routine use in patients with cardiac arrest.…”
Section: Concept and Definition Of Extracorporeal Cardiopulmonary Resmentioning
confidence: 99%